Codification of Islamic Law in Comparative Perspective: Between Tradition and Modernity - Lukito, Ratno; Az-Zahra, Marsya Salsabilla (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2026)
This paper examines the transformation of Islamic law through the process of codification from a comparative legal perspective. While classical Islamic law was traditionally pluralistic, jurist-driven, and uncodified, modern developments, especially since the 19th century, have seen states systematically incorporate Islamic legal principles into codified legal systems. The study explores how codification, influenced by European civil law models, reshapes the epistemology and authority of Islamic law, shifting interpretation from scholars to state actors. Through comparative case studies such as the Ottoman Majalla, Egypt, Iran, Malaysia, and Indonesia, the paper illustrates diverse models of codification ranging from centralized statutory codes to non-legislative presidential directives. The analysis highlights key debates around legal pluralism, gender reform, and the tension between tradition and state centralization. Codification, the paper argues, is not merely a legal technique but a transformative process that redefines the relationship between divine law and state sovereignty, producing hybrid legal systems that negotiate between Islamic authenticity and modern legal rationality.